Ajaran-Ajaran Syiah: Refleksi Dari Masyarakat Aceh - Abidin Nurdin; Al Chaidar; Muhammad bin Abubakar (SIASAT, 2019)
In the Shiite (Syiah) concept, human leadership is rooted in Divine leadership. Allah chose man as the caliph on earth. For human salvation, He chose men who already have perfection in the nature and development of their personality. These humans are the Prophets who become priests in religious matters, and leaders in social affairs. The Prophets were followed by the Aushiya (testament recipients). From the aushiya continued by the fakih. Human leadership is thus the existence of God's leadership over humans. At this point, the Shiites believe in a unity of leadership, namely worldly leadership (social government) and spiritual leadership (spiritual religion). But what's interesting is that selection to become a fakih is very difficult and extra tight. Therefore, it is not difficult to find among the Shiites a bureaucratic elite leader who is proficient and has deep knowledge of his religion in a person at once